An Adaptive Fuzzy-Logic Traffic Control System in Conditions of Saturated Transport Stream - N. R. Yusupbekov; A. R. Marakhimov; H. Z. Igamberdiev; Sh. X. Umarov (The Scientific World Journal)
This paper considers the problem of building adaptive fuzzy-logic traffic control systems (AFLTCS) to deal with information fuzziness and uncertainty in case of heavy traffic streams. Methods of formal description of traffic control on the crossroads based on fuzzy sets and fuzzy logic are proposed. This paper also provides efficient algorithms for implementing AFLTCS and develops the appropriate simulation models to test the efficiency of suggested approach.